Implications of the Urban Landscape: Aspects of the Isan Cultural Maintenance and Revitalization Program - Draper, John (Journal of Urban Culture Research, 2017)
This article describes the multilingual landscape aspect of the Isan Culture Maintenance and Revitalization Programme (ICMRP), a 500,000-euro, four-year European Union co-sponsored cultural maintenance and revival project focusing on the Thai Lao, Thailand’s largest ethnic minority community, in four municipalities in Northeast Thailand. The article begins by situating the multilingual landscape of the ICMRP within a holistic project, including manufacturing ‘ethnic’ student and municipal uniforms, teaching Isan as a mother tongue, recording a multimedia cultural archive, and designing and installing multilingual signage. It then argues the ICMRP’s multilingual landscape should be understood within a framework involving geosemiotics, the linguistic landscape, and language policy and planning. The ICMRP’s multilingual landscape contributes to the standardisation of a Thai Lao alphabet and spelling. It also seeks to officialise Thai Lao, through official signage, and thereby promote Thai Lao’s revival, as part of meeting Thailand’s human rights obligations as well as ASEAN community building.